The palm or the plate? An assessment of dietary guideline promotion, awareness, and preferences among Saudis: cross-sectional survey - Aroub Alnasser (BMC, 2023)
Abstract Background Dietary Guidelines for Saudis are offered and promoted in two forms: the Healthy Food Palm and the Saudi Healthy Plate. However, public awareness, recognition, and engagement with these guidelines is not well studied. Understanding the factors behind dietary guideline promotion, awareness, recognition, and use may lead to greater optimization of and engagement with the guidelines. This study aims to assess recognition of and public engagement with the My Palm and My Plate dietary guidelines as well as dietary guideline awareness, perceptions, and preferences among Saudis. Methods To compare awareness, knowledge, and usability between the Healthy Food Palm and the Saudi Healthy Plate dietary guidelines, a cross-sectional survey-based study was conducted among Saudi adult males and females above 18 (n = 674) between October 2021 and January 2022. Participants were split into groups based on age and gender. T-test and χ2 tests were used to determine differences between groups for continuous and categorical variables, respectively. Results Most participants were unaware of the Healthy Food Palm and the Saudi Healthy Plate guidelines, with only 11.1% and 30.3% able to recognize guideline-associated visual illustrations, respectively. However, nearly half of the participants correctly identified the number of food groups in the Healthy Food Palm and Saudi Healthy Plate. As well, more than half of the sample preferred the Saudi Healthy Plate, while one-quarter of the sample preferred neither guideline. In terms of future public health promotion, participants identified that "convenience and availability" (29.6%) and "my own health" (28.6%) were the most influential dietary choice factors with "social media campaigns" (2.4%) and the involvement of "an influencer" (3.1%) being the least influential dietary choice factors. Conclusions Implementation of and public awareness of dietary guidelines is less than optimal, and opportunities exist for greater information dissemination and public engagement. Measurement and ongoing evaluation of public dietary guideline awareness and use and a more in-depth understanding of dietary choice influences and behaviors are important considerations for dietary guideline development and promotion.